2020
DOI: 10.1101/2020.12.03.20243113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the calibration of confidence judgments in individuals with schizophrenia spectrum disorders

Abstract: BackgroundMetacognitive deficits are well documented in schizophrenia spectrum disorders as a decreased capacity to adjust confidence to first-order performance in a cognitive task. Because metacognitive ability directly depends on first-order performance, observed metacognitive deficits might be driven by lower first-order performance. We aimed to determine the extent to which individuals with schizophrenia experience specific deficits when producing confidence judgments and examined whether studies controlli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Deficits in metacognitive capabilities are thought to be a central aspect of schizophrenia, 52 , 53 but see, 73 and have been related to reduced neurocognitive capabilities and social functioning. 74 While recent findings have suggested that schizophrenia patients have comparable metacognitive abilities for low level perceptual decisions 73 , 75 the current deficit in metacognition for SoA judgments most likely relates to a meta-executive level in which the sensorimotor conflict induces a conscious and explicit assessment of the authorship of the action. 64 This is in line with the prominent meta-executive deficits in schizophrenia as found for insight into illness and hallucinations.…”
Section: Discussionmentioning
confidence: 92%
“…Deficits in metacognitive capabilities are thought to be a central aspect of schizophrenia, 52 , 53 but see, 73 and have been related to reduced neurocognitive capabilities and social functioning. 74 While recent findings have suggested that schizophrenia patients have comparable metacognitive abilities for low level perceptual decisions 73 , 75 the current deficit in metacognition for SoA judgments most likely relates to a meta-executive level in which the sensorimotor conflict induces a conscious and explicit assessment of the authorship of the action. 64 This is in line with the prominent meta-executive deficits in schizophrenia as found for insight into illness and hallucinations.…”
Section: Discussionmentioning
confidence: 92%
“…Expected metacognitive sensitivity thus strongly depends on type 1 performance. Indeed, the importance of such type 1 performance confounds has been demonstrated in a recent meta-analysis of metacognitive performance aberrancies in schizophrenia ( Rouy et al, 2020 ). The authors found that a previously claimed metacognitive deficit in schizophrenia was present only in studies that did not control for type 1 performance.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits of metacognitive capacities are well documented across the schizophrenia spectrum and has been related to poorer outcomes (Dietrichkeit et al, 2020;Hasson-Ohayon et al, 2018;Koren et al, 2006;Lysaker et al, 2011). However, recent work on perceptual metacognition indicates that when task difficulty is stringently controlled, metacognitive deficits in schizophrenia are small or even absent (Faivre, Roger, et al, 2020;Powers et al, 2017;Rouy et al, 2021). The current study examining embodied SoA in patients, found an extensive deficit in SoA discrimination, combined with high confidence in their judgments pointing to a considerable deficit in metacognition for SoA (although, one must take into account that first order performance was not equated here, which may account for some of the differences between the groups, see Rouy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work on perceptual metacognition indicates that when task difficulty is stringently controlled, metacognitive deficits in schizophrenia are small or even absent (Faivre, Roger, et al, 2020;Powers et al, 2017;Rouy et al, 2021). The current study examining embodied SoA in patients, found an extensive deficit in SoA discrimination, combined with high confidence in their judgments pointing to a considerable deficit in metacognition for SoA (although, one must take into account that first order performance was not equated here, which may account for some of the differences between the groups, see Rouy et al, 2021). This suggests that in contrast to low-level perceptual metacognitive capacities which may be preserved, metacognition of SoA involving the integration of sensorimotor signals and higher-order constructs such as beliefs and intentions is severely impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation